2006
DOI: 10.1089/jpm.2006.9.716
|View full text |Cite
|
Sign up to set email alerts
|

The Seattle Pediatric Palliative Care Project: Effects on Family Satisfaction and Health-Related Quality of Life

Abstract: Pediatric palliative care services that focus on effective communication, decision support, and co-case management with insurers can improve aspects of quality of life and family satisfaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
142
0
5

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 152 publications
(149 citation statements)
references
References 17 publications
2
142
0
5
Order By: Relevance
“…Studies were eligible if they included a comprehensive PPCP or its components (e.g., palliative care consultation, respite care, end-of-life care or planning, hospice and community-based palliative care) and they exclusively included children with life-threatening conditions who were 22 years of age or younger. Although there is no consistency to the upper age limit in this population, 1,5 programs can support transition to adult palliative care services up to the age of 22 (e.g., the Seattle Pediatric Palliative Care Project 6 ).…”
mentioning
confidence: 99%
“…Studies were eligible if they included a comprehensive PPCP or its components (e.g., palliative care consultation, respite care, end-of-life care or planning, hospice and community-based palliative care) and they exclusively included children with life-threatening conditions who were 22 years of age or younger. Although there is no consistency to the upper age limit in this population, 1,5 programs can support transition to adult palliative care services up to the age of 22 (e.g., the Seattle Pediatric Palliative Care Project 6 ).…”
mentioning
confidence: 99%
“…Communication within the pediatric palliative care context requires contact among many sources (e.g., insurance providers, medical professionals, psychosocial clinicians, and spiritual experts), which can be challenging. However, results from the study suggest patient quality of life and family satisfaction for children with life-threatening illness can be improved with integrated pediatric palliative care (Hays et al, 2006).…”
Section: Palliative Care: Recipientsmentioning
confidence: 97%
“…In an empirical study of pediatric palliative care, Hays et al (2006) found several care processes that blended curative and comfort care to improve parent perceptions and parent satisfaction of their child's quality of life. A key factor is effective communication between the parents and providers that support patient preferences.…”
Section: Palliative Care: Recipientsmentioning
confidence: 99%
See 2 more Smart Citations